Dr. Zurinah Hassan / Norsalwa Mat Isa and Wan Nurul Hazira W. Mahmood - Mat Isa, Norsalwa; W. Mahmood, Wan Nurul Hazira (2011)
Dr. Zurinah Hassan is a famous author in writing poetic work. She started writing since she was twelve years old. She has involved in this field about 50 years. She took first degree at University Science Malaysia, second degree at University Putra Malaysia and PhD at University of Malaya. She was very active in writing poetic even though she was working at that time. Her writings have been published in newspaper and magazine publisher like Dewan Bahasa, Dewan Masyarakat, Utusan Melayu, Mastika and othesr. Her writing win many of the competitions that she took like SEA Writer Award, lHadiah Sastera Perdana', 'Hadiah Buku Perpustakaan Negara', 'Anugerah Puisi Putera', and she scored first place in Poetic Competition. Other than that, she also gets second place for 'Anugerah Tokoh Wanita Selangor 2007'. Sesayup Jalan, Di Sini Tiada Perhentian, Pujangga Tidak Bernama, Memoir Zurinah Hassan, Nota Waktu, Pasanan Dari Gunung Ledang and many more are her entire writing that had been published. Other than writing, she was also active in reading poems, being judges for poetic competition, as an instructor for new comers in this field, PPS (Persatuan Penulis Selangor) Committee and Selangor Museum Committee.